Enhanced recovery of heavy oil using a catalytic process - Hasan, Muayad Mohammed (2018)
Oil is a major source of energy around the world. With the decline of light conventional oil, more attention is being paid to heavy oil and bitumen, as a good alternative to light oil for energy supplies. Heavy crude oils have a tendency to have a higher concentration of metals and several other elements such as sulfur and nitrogen, and extraction of these heavy oils requires more effort and cost. The Toe-to-heel Air Injection catalytic upgrading process In-situ (THAI-CAPRI) is an integrated process which includes recovery and upgrading of heavy oil and bitumen using an air injection process, and horizontal injector and producer wells. Since the process works through a short distance displacement technique, the produced oil flows easily toward the horizontal producer well. This direct mobilized oil production and short distance are the major properties of this method which lead to robust operational stability and high oil recovery. This technique gives the possibility of a higher recovery percentage and lowers environmental effects compared to other technologies like steam based techniques. A catalyst plays a crucial role in the THAI-CAPRI technique to be successfully conducted. However, heavy coke can be formed as a result of the thermal cracking of heavy oil occurring in the THAI-CAPRI process, and a catalyst resistant enough to use in CAPRI needs to be developed. Therefore, there is a need to understand the pore structure to achieve a high catalyst quality, to obtain a structure that directly affects the fluid behaviour within a disordered porous material. In this study, novel experimental techniques were used to obtain greater accuracy results, for the information obtained from gas adsorption curves by using a combination of data obtained for two adsorptives, namely nitrogen and argon, both before and after mercury porosimetry. This new method allows studying the effect of pore-pore co-operative during an adsorption process, which significantly affects the accuracy of the pore size distributions, obtained for porous solids. A comparison, between the results obtained from the characterisation of a mixed silica-alumina pellet and those obtained from pure silica and alumina catalysts, were presented to study the effects of surface chemistry on the different wetting properties of adsorbates. The pore networks within pellets invaded by mercury following mercury porosimetry have been imaged by computerized X-ray tomography (CXT). It was noticed that the silica-alumina catalyst had a hierarchical internal structure, similar to that for blood vessels in the body. To validate the findings of the pore geometry characterisation obtained from the new method, several techniques, such as cryoporometry, gas sorption isotherms, and mercury intrusion experiments, were considered. Further, a novel well design consisting of two horizontal injectors and two horizontal producers was used in different well configurations, to investigate the potential for improved efficiency of the THAI process on the heavy oil recovery. A 3D dimensional simulation model, employing the CMG-STARS simulator, was applied in this simulation. Two horizontal injectors and producers were designed in this project, instead of horizontal injector and producer were used in the Greaves model (the base case model), to investigate the effect of the extra injector and producer on the performance of the THAI process. It was found that the locations of the well injections and the well productions significantly affected the oil production. For the study of the effectiveness of the catalysts in the oil upgrading process, the CAPRI technique has been simulated to investigate the effect of several parameters, such as catalyst packing porosity, the thickness of the catalyst layer and hydrogen to air ratio, on the performance of the CAPRI process. The TC3 model used by Rabiu Ado (2017), which was the same model used in the experimental study of Greaves et al. (2012), was also used in this study. The Houdry catalyst characterised by the experimental work was placed around the horizontal producer in this simulation.